Temporal changes in the levels of virus and betasatellite DNA in B. tabaci feeding on CLCuD affected cotton during the growing season - Iqbal, Zafar; Masood, Mariyam; Shafiq, Muhammad; Briddon, Rob W. (Frontiers in Microbiology, 2024)
Cotton, a key source of income for Pakistan, has suffered significantly by Cotton leaf curl disease (CLCuD) since 1990. This disease is caused by a complex of phylogenetically-related begomovirus (genus Begomovirus, family Geminiviridae) species and a specific betasatellite (genus Betasatellite, family Tolecusatellitidae), Cotton leaf curl Multan betasatellite. Additionally, another DNA satellite called alphasatellite (family Alphasatellitidae), is also frequently associated. All these virus components are vectored by a single species of whitefly (Bemisia tabaci). While many factors affect cotton productivity, including cotton variety, sowing time, and environmental cues such as temperature, humidity, and rainfall, CLCuD is a major biotic constraint. Although the understanding of begomoviruses transmission by whiteflies has advanced significantly over the past three decades, however, the in-field seasonal dynamics of the viruses in the insect vector remained an enigma. This study aimed to assess the levels of virus and betasatellite in whiteflies collected from cotton plants throughout the cotton growing season from 2014 to 2016. Notably, begomovirus levels showed no consistent pattern, with minimal variations, ranging from 0.0017 to 0.0074 ng.µg -1 of the genomic DNA in 2014, 0.0356 to 0.113 ng.µg -1 of the genomic DNA in 2015, and 0.0517 to 0.0791 ng.µg -1 of the genomic DNA in 2016. However, betasatellite levels exhibited a distinct pattern. During 2014 and 2015, it steadily increased throughout the sampling period (May to September). While 2016 showed a similar trend from the start of sampling (July) to September but a decline in October (end of sampling). Such a study has not been conducted previously, and could potentially provide valuable insights about the epidemiology of the virus complex causing CLCuD and possible means of controlling losses due to it.